Analysis of the Talented Towards Prophetic Wave Series of Films - Adriyani, Sabrina; Hartini, Tri Isti; Ermawati, Imas Ratna (International Journal of Research and Community Empowerment, 2024)
The study of scientific education, media studies, and moral instruction is one of the important studies in character education, especially in physics education. The research aims to investigate the relationship between wave material and the Gifted serial films and to determine the prophethood of the Gifted serial films and their relevance to students. The research method used was qualitative research with a descriptive approach. The primary data sources were observations, interviews, and documentation from students of class XI MAN 14 Jakarta, and secondary data was collected from literature and documents. The study's significant finding is the link between wave material and gifted serial films, specifically transverse waves, which include light and electromagnetic waves, and longitudinal waves, which include sound waves and brain waves. The prophethood of gifted serial films and their relevance to students was found to be significant, with Siddiq, Amanah, Fathonah, and Tabligh being the most prophetic. The results also showed a prophetic connection between The Gifted series and wave material. The prophetic link to the students was of a character, trustworthiness, and prophetic nature, as well as Fatonah. Therefore, The Gifted series can be used as material, particularly for transverse waves.